Map and compass navigation: the mechanism and ontogeny of animal maps - Joe Morford; Joe Wynn; Patrick Lewin; Paris Jaggers; Lewis Lancaster-Reeves; Adelaide Sibeaux; Oliver Padget; Tim Guilford (Animal Behaviour, 2025)

Pre-laying sex differences in reproductive roles can constrain foraging behaviour in a monomorphic seabird - Katrina Siddiqi-Davies; Lewis Lancaster-Reeves; Joe Morford; Oliver Padget; Joe Wynn; Sarah Bond; Patrick Lewin; Paris Jaggers; Tim Guilford (Marine Biology, 2025)
Sex differences in foraging behaviour can arise in monomorphic species when reproductive roles differ. How these differences shape foraging behaviour during the pre-laying period—an understudied reproductive stage in seabirds—remains unclear. In a monomorphic procellariform seabird, the Manx shearwater ( Puffinus puffinus ), we compare foraging behaviour between sexes during pre- and post-laying periods. Prior to laying, sex roles differ, with females synthesizing the egg, while males are thought to primarily engage in nest defence. We found that pre-laying females take longer at-sea trips that are more distant from the colony, whilst males visit the colony more frequently, and undertake more dives. For males, pre-laying dives are shallower than those during the post-laying period. Sex differences largely diminish post-laying, as reproductive roles become more equivalent between sexes. We suggest that increased colony visitation during pre-laying may constrain males to closer foraging sites and these may be of poorer quality than those reached by females. We found that colony visitation appears to restrict evening foraging opportunities for males, as birds must commute to the breeding site for nocturnal visits. Our results show that significant differences in reproductive roles before egg-laying can constrain at-sea foraging behaviour. Understanding these differences can facilitate understanding of how sex-specific foraging behaviour may interact with human-induced changes in marine environments.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)